Current status of islet xenotransplantation. (November 2015) - Park, Chung-Gyu; Bottino, Rita; Hawthorne, Wayne J.
Abstract: Cell therapy for Type 1 diabetes (T1D) utilizing islet cell transplantation can successfully restore endogenous insulin production in affected patients. Islet cell engraftment and survival are conditional on the use of efficacious anti-rejection therapies and on the availability of healthy donor cells. The scarcity of healthy human donor pancreata is a limiting factor in providing sufficient tissue to meet the demand for islet transplantation worldwide. A potential alternative to the use of cadaveric human donor pancreases is the use of animal sourced islets. Pancreatic islets obtained from pigs have emerged as an alternative to human tissues due to their great availability, physiological similarities to human islets, including the time-tested use of porcine insulin in diabetic patients and the ability to genetically modify the donor source. The evolution of refined, efficacious immunosuppressive therapies with reduced toxicity, improvements in donor management and genetic manipulation of the donor have all contributed to facilitate long-term function in pre-clinical models of pig islet grafts in non-human primates. As clinical consideration for this option is growing, and trials involving the use of porcine islets have begun, more compelling experimental data suggest that the use of pig islets may soon become a viable, safe, effective and readily available treatment for insulin deficiency in T1D patients. Highlights: Pancreatic islet transplantation can treat Type 1 diabetes (T1D) patients. Organ shortage limits the wide application of Islet transplantation. Porcine islets can be an alternative islet source by providing unlimited good quality of islets. Current pig to non-human primate islet xenotransplantation study showed successful long-term control of diabetes. Porcine islet xenotransplantation comes much closer to clinical realization.